Retrograde signals from endosymbiotic organelles: a common control principle in eukaryotic cells. (22nd June 2020) - Pfannschmidt, Thomas; Terry, Matthew J.; Van Aken, Olivier; Quiros, Pedro M.
Abstract : Endosymbiotic organelles of eukaryotic cells, the plastids, including chloroplasts and mitochondria, are highly integrated into cellular signalling networks. In both heterotrophic and autotrophic organisms, plastids and/or mitochondria require extensive organelle-to-nucleus communication in order to establish a coordinated expression of their own genomes with the nuclear genome, which encodes the majority of the components of these organelles. This goal is achieved by the use of a variety of signals that inform the cell nucleus about the number and developmental status of the organelles and their reaction to changing external environments. Such signals have been identified in both photosynthetic and non-photosynthetic eukaryotes (known as retrograde signalling and retrograde response, respectively) and, therefore, appear to be universal mechanisms acting in eukaryotes of all kingdoms. In particular, chloroplasts and mitochondria both harbour crucial redox reactions that are the basis of eukaryotic life and are, therefore, especially susceptible to stress from the environment, which they signal to the rest of the cell. These signals are crucial for cell survival, lifespan and environmental adjustment, and regulate quality control and targeted degradation of dysfunctional organelles, metabolic adjustments, and developmental signalling, as well as induction of apoptosis. The functional similarities between retrograde signalling pathways in autotrophic and non-autotrophic organisms are striking, suggesting the existence of common principles in signalling mechanisms or similarities in their evolution. Here, we provide a survey for the newcomers to this field of research and discuss the importance of retrograde signalling in the context of eukaryotic evolution. Furthermore, we discuss commonalities and differences in retrograde signalling mechanisms and propose retrograde signalling as a general signalling mechanism in eukaryotic cells that will be also of interest for the specialist. This article is part of the theme issue 'Retrograde signalling from endosymbiotic organelles'.